2003
DOI: 10.1002/prs.680220102
|View full text |Cite
|
Sign up to set email alerts
|

Further uses of the heat of oxidation in chemical hazard assessment

Abstract: Flammability: The “net heat of oxidation” technique described in an earlier publication is extended to predicting the lower flammable limits, lower limit flame temperatures, and limiting oxygen concentrations of chlorinated organic fuels having H:Cl ratios greater than unity. A new Rule is derived for predicting the effect of initial temperature on the lower flammable limits and limiting oxygen concentrations of organic fuels. It is suggested that this Rule be used in preference to the modified “Burgess‐Wheele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 13 publications
0
34
0
Order By: Relevance
“…In connection with the temperature dependence of flammability limits, White reported that the limit flame temperature is kept constant independently of the experimental temperature [10]. If it is the case, the lower flammability limits change linearly to temperature [11][12][13]. Among others, Zabetakis investigated systematically to demonstrate the linear temperature dependence of lower flammability limits of saturated hydrocarbons [12].…”
Section: Introductionmentioning
confidence: 99%
“…In connection with the temperature dependence of flammability limits, White reported that the limit flame temperature is kept constant independently of the experimental temperature [10]. If it is the case, the lower flammability limits change linearly to temperature [11][12][13]. Among others, Zabetakis investigated systematically to demonstrate the linear temperature dependence of lower flammability limits of saturated hydrocarbons [12].…”
Section: Introductionmentioning
confidence: 99%
“…This equation is shown to be valid only for linear hydrocarbons [13]. To estimate the effect of temperature on the LFL, Britton and Frurip [14] recommend the following equation: where L T is the LFL (in mol %) at the temperature of interest T (in K), L 0 is the known experimental or estimated value of the LFL at a temperature T T (in K), and LLFT is the lower limit flame temperature (in K). Most of the previous studies did not discuss the reliability of the experimental LFL data reported in the literature (except briefly in Britton's studies).…”
Section: Scope Of This Studymentioning
confidence: 99%
“…Britton and Frurip (2003) have summarized and amplified the above findings for the temperature dependence of the LFL. They explicitly included a variable limiting flame temperature (T f ) to give (5) where L o and T o refer to the ambient or test temperature (all temperatures are consistently either in °C or K, and C L = 1/(T f − T o ).…”
Section: Theory: Limit Flame Temperature -Mixture Combustion Energymentioning
confidence: 99%
“…Britton and Frurip (2003) used T f = 1440 K for "typical" hydrocarbons, T f = 1505 K for other "typical" organic (CHON) fuels, and T f = 1580 K for chlorinated organic compounds. Hence the single limit flame temperature used previously has been replaced by Britton and Frurip with three such limits for the various types of organic fuels (hydrocarbons, oxygenated organics, and halogenated organic fuels).…”
Section: Theory: Limit Flame Temperature -Mixture Combustion Energymentioning
confidence: 99%
See 1 more Smart Citation